Overview of Next‐Generation Sequencing Technologies. Issue 1 (16th April 2018) - Slatko, Barton E.; Gardner, Andrew F.; Ausubel, Frederick M.
Abstract: High throughput DNA sequencing methodology (next generation sequencing; NGS) has rapidly evolved over the past 15 years and new methods are continually being commercialized. As the technology develops, so do increases in the number of corresponding applications for basic and applied science. The purpose of this review is to provide a compendium of NGS methodologies and associated applications. Each brief discussion is followed by web links to the manufacturer and/or web‐based visualizations. Keyword searches, such as with Google, may also provide helpful internet links and information. © 2018 by John Wiley & Sons, Inc.